Towards Information Quality Assurance in Spanish: Wikipedia - Ferretti, Edgardo (2017)
Featured Articles (FA) are considered to be the best articles that Wikipedia has to offer and in the last years, researchers have found interesting to analyze whether and how they can be distinguished from “ordinary” articles. Likewise, identifying what issues have to be enhanced or fixed in ordinary articles in order to improve their quality is a recent key research trend. Most of the approaches developed to face these information quality problems have been proposed for the English Wikipedia. However, few efforts have been accomplished in Spanish Wikipedia, despite being Spanish, one of the most spoken languages in the world by native speakers. In this respect, we present a breakdown of Spanish Wikipedia’s quality flaw structure. Besides, we carry out studies with three different corpora to automatically assess information quality in Spanish Wikipedia, where FA identification is evaluated as a binary classification task. Our evaluation on a unified setting allows to compare with the English version, the performance achieved by our approach on the Spanish version. The best results obtained show that FA identification in Spanish, can be performed with an F1 score of 0.88 using a document model consisting of only twenty six features and Support Vector Machine as classification algorithm.